Aging With Multiple Sclerosis: Age-Related Factors and Socioeconomic Risks - Wandall-Holm, Malthe Faurschou; Andersen, Mads Albrecht; Buron, Mathias Due; Magyari, Melinda (Frontiers in Neurology, 2022)
Background Studies have demonstrated an increasing mean age of the population with Multiple Sclerosis (MS). The association between increased age and socioeconomic outcomes have been investigated sparsely. Objective To describe the demographic and socioeconomic status of the current Danish population of patients with MS according to age and to assess the age-related risks of no income/losing all income from earnings or receiving disability pension. Methods The nationwide population-based Danish Multiple Sclerosis Registry provided data linked with the Danish population and income statistics registry and Danish Rationale Economic Agents Model (DREAM) database. Prevalence of socioeconomic milestones of the current MS population was compared with healthy controls and the risks of reaching socioeconomic milestones were assessed using cause-specific Cox models and cumulative incidence functions compared to healthy controls. Results The current Danish population of patients with MS of working age (18-65 years of age) consists of 11.287 patients, of which 29.3% was older than 55 years. In 2018, 38.0% of all patients and 18.9% of controls had no income from earnings, while 30.5% of all patients and 7.7% of controls received disability pension. The risk of losing all income from earnings was higher for MS patients with a hazard ratio (HR) peaking at of 4.0 (95% CI, 3.8-4.2) for the 45-54 years old. The risk of receiving disability pension was much higher for MS patients peaking at a HR of 22.6 (95% CI, 20.9-24.4) for the 25-34 years old. Likewise, the absolute risks of both outcomes were higher for the MS patients at all ages. Conclusion Danish persons with MS are at a higher risk of losing all income from earnings and at a much higher risk of receiving disability pension compared with healthy controls.